Initiation of lactation and the provision of human milk to preterm infants in German neonatal intensive care units from the mothers' perspective - N. Scholten; L. Mause; D. Horenkamp-Sonntag; M. Klein; T. Dresbach (BMC, 2022)
Abstract Background If infants with a very low birth weight (VLBW) are to be fed exclusively with human milk, it is essential to focus on lactation initiation. The aim of the study is to learn more about the current state of lactation initiation and human milk provision in neonatal intensive care units in Germany from the mothers' perspective. Methods Written surveys were conducted with mothers of VLBW infants to learn more about the timing of initiation of lactation, pumping frequency during the first three days postpartum and feeding of the preterm infant during hospitalisation. Results The data of 437 mothers (response rate: 44.7%) were included in the analyses. Of these, only 7.8% stated that they had initiated lactation immediately after delivery and 38.2% within 6 h. In terms of pumping frequency, 50.1% pumped 7-9 times a day within the first 3 days postpartum; 60.9% reported that their infant received formula feedings during the hospital stay. Conclusion Overall, deficits were still evident with regard to the initiation of lactation in mothers of VLBW infants in Germany, resulting in a large proportion of VLBW infants receiving formula in the hospital. Trial registration German Clinical Trial Register: DRKS00017755 .